An evaluation of post- Yolanda programs on agriculture the case of coconut industry in Burauen, Leyte - Auza, Johnmark Gabriel G.; Baranda, Earl Lester O.; Ledda, Ariel Alexis B.; Tamayo, Kenneth R.; Pormon, Miah Maye M. (2017)
The aftermath of super typhoon Yolanda caused a massive decline in the coconut production and greatly affected the economic performance of Eastern Visayas. In response to this problem, the government offered programs for the rehabilitation of the coconut industry. Given these rehabilitation process, the researchers evaluated the impact of these programs to the coconut farmers. Moreover, the paper identified the post-Yolanda programs, determine its impacts and enumerate recommendations for the programs to be improved. The researchers constructed the Hierarchical Evaluation Model to assess the impact of these programs. Data were collected through key informant interviews with the officials of PCA and Department of Agriculture of Burauen, Leyte. Focus group discussions were also conducted among the 40 coconut farmers in four barangays of Burauen, Leyte. Likert Scale and One-way ANOVA were utilized to measure the responses and to determine the differences between responses, respectively. Results show that the responses of farmers per barangay is significant, implying that the perception of the farmers to the programs implemented vary in every barangay. Moreover, there were four programs implemented: Coconut Planting/Replanting, Coconut Debris Management, Coconut Fertilization and Intercropping. However, not all farmers were able to avail the said programs which made the condition of livelihood unchanged. Furthermore, the farmers suggested that budgeting is the most important stage in project implementation. The study recommends that the government should implement all programs equally to farmers and hasten the processes involved. Moreover, to make use of the programs effectively and efficiently, the government should provide trainings and seminars regarding coconut farming. Finally, the researchers recommend that the government should introduce new farming methods that will yield more coconut in a short period of time.
Undergraduate thesis (BASS Economics) -- University of the Philippines, Tacloban.